Cyclin-Dependent Kinase 8 Represents a Positive Regulator of Cytomegalovirus Replication and a Novel Host Target for Antiviral Strategies - Obergfäll, Debora; Wild, Markus; Sommerer, Mona; Barillas Dahm, Malena; Kicuntod, Jintawee; Tillmanns, Julia; Kögler, Melanie; Lösing, Josephine; Dhotre, Kishore; Müller, Regina; Wangen, Christina; Wagner, Sabrina; et al. (Pharmaceutics, 2024)
Background. Cyclin-dependent kinase 8 (CDK8) is a multifaceted regulator and represents a catalytic component of the transcriptional Mediator complex. CDK8 activity, on the one hand, increases transcriptional elongation by the recruitment of Mediator/super elongation complexes, but, on the other hand, negatively regulates CDK7-controlled transcriptional initiation through inactivating cyclin H phosphorylation. Recently, these combined properties of CDK8 have also suggested its rate-limiting importance for herpesviral replication. Objectives. In this paper, we focused on human cytomegalovirus (HCMV) and addressed the question of whether the pharmacological inhibition or knock-down of CDK8 may affect viral replication efficiency in cell culture models. Methods. A number of human and animal herpesviruses, as well as non-herpesviruses, were used to analyze the importance of CDK8 for viral replication in cell culture models, and to assess the antiviral efficacy of CDK8 inhibitors. Results. Using clinically relevant CDK8 inhibitors (CCT-251921, MSC-2530818, and BI-1347), HCMV replication was found strongly reduced even at nanomolar drug concentrations. The EC50 values were consistent for three different HCMV strains (i.e., AD169, TB40, and Merlin) analyzed in two human cell types (i.e., primary fibroblasts and astrocytoma cells), and the drugs comprised a low level of cytotoxicity. The findings highlighted the following: (i) the pronounced in vitro SI values of anti-HCMV activity obtained with CDK8 inhibitors; (ii) a confirmation of the anti-HCMV efficacy by CDK8–siRNA knock-down; (iii) a CDK8-dependent reduction in viral immediate early, early, and late protein levels; (iv) a main importance of CDK8 for viral late-stage replication; (v) several mechanistic aspects, which point to a strong impact on viral progeny production and release, but a lack of CDK8 relevance for viral entry or nuclear egress; (vi) a significant anti-HCMV drug synergy for combinations of inhibitors against host CDK8 and the viral kinase vCDK/pUL97 (maribavir); (vii) finally, a broad-spectrum antiviral activity, as seen for the comparison of selected α-, β-, γ-, and non-herpesviruses. Conclusions. In summary, these novel data provide evidence for the importance of CDK8 as a positive regulator of herpesviral replication efficiency, and moreover, suggest its exploitability as an antiviral target for novel strategies of host-directed drug development.
CRIS-Team Scopus Importer:2024-10-04
Keywords: antiviral approach with CDK8-inhibitory small molecules; broad-spectrum antiviral CDK8 inhibitors; cyclin-dependent kinase 8 (CDK8); human cytomegalovirus (HCMV); human pathogenic herpesviruses; negative impact of CDK8 inhibitors; novel host-directed targeting strategies; regulation of viral replication; siRNA-mediated CDK8 knock-down; virus-supportive cellular protein kinases

Establishment of a Luciferase-Based Reporter System to Study Aspects of Human Cytomegalovirus Infection, Replication Characteristics, and Antiviral Drug Efficacy - Tillmanns, Julia; Kicuntod, Jintawee; Ehring, Antonia; Elbasani, Endrit; Borst, Eva Maria; Obergfäll, Debora; Müller, Regina; Hahn, Friedrich; Marschall, Manfred (Pathogens, 2024)
Human cytomegalovirus (HCMV) represents a highly medically important pathogen which has constantly been the subject of both molecular and clinical investigations. HCMV infections, especially those in high-risk patients, still raise many unanswered questions, so current investigations are focused on viral pathogenesis, vaccine development, and options for antiviral drug targeting. To this end, the use of suitable viral strains as well as recombinant reporter constructs in cultured cells and model systems has specific significance. We previously reported on the application of various herpesviruses that express green, red, or related fluorescent proteins, especially in the fields of virus–host interaction and antiviral research. Here, we characterized a recombinant version of the clinically relevant and cell type-adaptable HCMV strain TB40, which expresses firefly luciferase as a quantitative reporter of viral replication (TB40-FLuc). The data provide evidence for five main conclusions. First, HCMV TB40-FLuc is employable in multiple settings in primary human cells. Second, viral reporter signals are easily quantifiable, even at early time points within viral replication. Third, the FLuc reporter reflects the kinetics of viral intracellular replication, cascade-like viral IE-E-L protein production, and progeny release. Fourth, as relates to specific applications of the TB40-FLuc system, we demonstrated the reliability of quantitative antiviral compound determination in multi-well formats and its independence from fluorescence-based measurements in the case of autofluorescent inhibitors. Finally, we illustrated increased reporter sensitivity in comparison to other recombinant HCMVs. In essence, recombinant HCMV TB40-FLuc combines several molecular properties that are considered beneficial in studies on viral host tropism, replication efficiency, and antiviral drug assessment.
CRIS-Team Scopus Importer:2024-09-06
Keywords: advantages of the reporter system; antiviral drug development; firefly luciferase reporter (FLuc); future applications in molecular HCMV analysis; human cytomegalovirus (HCMV); infection of primary human cultured cells; medically important viral pathogens; recombinant HCMV TB40-FLuc; viral replication characteristics and efficiency